Math
posted by aramik .
Evaluate the piecewise defined function at the indicated values.
f(x) = x^2 if x < 0
x + 9 if x ≥ 0
f(−3) =
f(−2) =
f(0) =
f(2) =
f(3) =
Respond to this Question
Similar Questions

calculus
A function f(x) is said to have a removable discontinuity at x=a if: 1. f is either not defined or not continuous at x=a. 2. f(a) could either be defined or redefined so that the new function IS continuous at x=a. Let f(x)= x2+10x+26 … 
Math
First, give the technology formula for the given function and then use technology to evaluate the function for the given values of x. (Round your answers to four decimal places.) r(x) = 4x2 + 1/4x2 − 1; x = −1, 0, 1, ..., … 
calculus HELP
Find the values of a and b that make f continuous everywhere. f(x) = (x2 − 4)/(x − 2) if x < 2 ax2 − bx + 3 if 2 ≤ x < 3 4x − a + b if x ≥ 3 solve for a and b? 
biology
Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner? 
Grade 12 Calculus
Evaluate each of the following. Show all your calculations. a) f'(3) if f(x) = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X) = −3x^2 − 5x + 7 … 
calculus (gr 12)
Evaluate each of the following. Show all your calculations. a) f'(3) if f(x) = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X) = −3x^2 − 5x + 7 … 
calculus (gr 12)
Evaluate each of the following. Show all your calculations. a) f'(3) if f(x) = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X) = −3x^2 − 5x + 7 … 
Math
Evaluate the piecewise defined function at the indicated values. f(x) = x2 + 6x if x ≤ −1 x if −1 < x ≤ 1 −1 if x > 1 f(−2) = f(3/2) = f(−1) = f(0) = f(35) = 
Calculus
Find all values of a and b so that the following function is continuous for all x ∈ R. f(x) = −3a + 4x^5(b) x ≤ −1 ax − 2b −1 < x < 1 3x^2 − bx + a x ≥ 1 
Calculus (Need help)
Not sure how do do this. Please help? Find all values of a and b so that the function is continuous for all x E R. f(x)= −3a + 4(x^5)b x ≤ −1 { ax − 2b −1 < x < 1 3x^2 − bx + a x ≥ 1